The patching together of pivot-patterns in talk-in-interaction: On ‘double dislocations’ in French - Pekarek Doehler, Simona; Horlacher, Anne-Sylvie (My University, 2013)
This paper investigates syntactic pivot patterns in French talk-in-interaction. In our data, pivot patterns recurrently amalgamate what has classically been called 'left dislocation' and 'right dislocation', as in the following: ça je vais les prendre les feuilles 'thesei I will take themi the papersi'. Here, the pivotal element (je vais les prendre 'I will take them') consists of a clause; the pre- and the post-pivot are each composed of an NP (ça and les feuilles, respectively) that is co-indexed by means of a pronoun (les 'them') within the pivot-clause. The paper investigates the interactional work that speakers accomplish through the [NP-clause-NP] pivot pattern. Results show that this pattern is routinized to different degrees for different interactional purposes: while speakers employ sedimented formats for proffering assessments, they configure the pivot pattern ad hoc for managing reference formulation. In the latter case, the pattern is patched together on-line, incrementally, following an emergent trajectory by means of which speakers respond to interactional contingencies on a moment-to-moment basis. We conclude that pivot patterns can be understood as processual products, adapted in the very course of their production to the contingencies of talk-in-interaction. As such, they are part of an emerging grammar for all practical proposes.
Keywords: Pivot; Dislocation; On-line grammar; Assessment; Referential repair